2020
DOI: 10.1186/s12902-020-0538-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fetuin-A levels are increased and associated with insulin resistance in women with polycystic ovary syndrome

Abstract: Background: Insulin resistance (IR) is a common characteristic of women with polycystic ovary syndrome (PCOS). It has been reported that circulating Fetuin-A levels were associated with IR and type 2 diabetes mellitus (T2DM). However, previous reports were inconsistent. Methods: Two hundred seven subjects were screened for PCOS according to the diagnostic guideline of the Rotterdam consensus criterion. Serum Fetuin-A levels were measured using an ELISA kit. An independent t-test or Nonparametric test was used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
(34 reference statements)
3
10
0
Order By: Relevance
“…As reported previously, intralipid infusion dramatically increased plasma TG, and NEFA concentrations in control and PCOS women; and had no effects on cholesterol levels (15). Two-way RM ANOVA analysis comparing between control and PCOS showed a significant increase in FGF21 (P < 0.05) between the groups and no changes were observed for FGF19, FGF23, and Fetuin-A.…”
Section: Effects Of Intralipid and Combination Of Intralipid And Insusupporting
confidence: 77%
See 2 more Smart Citations
“…As reported previously, intralipid infusion dramatically increased plasma TG, and NEFA concentrations in control and PCOS women; and had no effects on cholesterol levels (15). Two-way RM ANOVA analysis comparing between control and PCOS showed a significant increase in FGF21 (P < 0.05) between the groups and no changes were observed for FGF19, FGF23, and Fetuin-A.…”
Section: Effects Of Intralipid and Combination Of Intralipid And Insusupporting
confidence: 77%
“…Previous studies have shown differences in circulating levels of endocrine FGFs (13,14) and fetuin-A (15) in PCOS women. FsGF21 and fetuin-A were reported to be elevated and FGF19 was found to be lower in PCOS women compared to healthy controls (13)(14)(15).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many putative molecules have been proposed to be involved in PCOS pathogenesis and related metabolic disturbances. Hepatokines, adipokines, myokines, and cytokines that have been reported to be associated with PCOS include, but are not limited to, Fetuin-A, lipocalin-2, adropin, leptin, and irisin [4][5][6][7]. It has long been known that women with PCOS appear to have a high risk for central obesity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity classification of the study groups was performed by using age and sex-adjusted BMI percentile tables prepared by World Health Organization. (27) Children with the values higher than 99th percentile were included into MO group. Obese group was composed of children,whose age-and sex-based BMI percentile values were between 95 and 99.…”
Section: Obesity Classificationmentioning
confidence: 99%